A Fourier transform Raman spectrometer with visible laser excitation. (14th January 2015) - Dzsaber, S.; Negyedi, M.; Bernáth, B.; Gyüre, B.; Fehér, T.; Kramberger, C.; Pichler, T.; Simon, F.
Abstract : We present the development and performance of a Fourier transformation (FT)‐based Raman spectrometer working with visible laser (532 nm) excitation. It is generally thought that FT‐Raman spectrometers are not viable in the visible range where shot noise limits the detector performance and therein they are outperformed by grating based, dispersive ones. We show that contrary to this common belief, the recent advances of high‐performance interference filters makes the FT‐Raman design a valid alternative to dispersive Raman spectrometers for samples which do not luminesce. We critically compare the performance of our spectrometer to two dispersive ones: a home‐built single channel and a state‐of‐the‐art charge coupled device‐based instruments. We demonstrate a similar or even better sensitivity than the charge coupled device‐based dispersive spectrometer particularly when the laser power density is considered. The instrument possesses all the known advantages of the FT principle of spectral accuracy, high throughput, and economic design. We also discuss the general considerations, which helps the community reassess the utility of the different Raman spectrometer designs. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We present the development and performance of a Fourier transformation (FT)‐based Raman spectrometer working with visible laser (532 nm) excitation. It is generally thought that FT‐Raman spectrometers are not viable in the visible range where shot noise limits the detector performance, and therein they are outperformed by grating‐based, dispersive ones. We show that contrary to this common belief, the recent advances of high‐performance interference filters makes the FT‐Raman design a valid alternative to dispersive Raman spectrometers for samples that do not luminesce. We critically compare the performance of our spectrometer with two dispersive ones: a home‐built single channel and a state‐of‐the‐art charge coupled device‐based instruments. We demonstrate a similar or even better sensitivity than the charge coupled device‐based dispersive spectrometer particularly when the laser power density is considered. The instrument possesses all the known advantages of the FT principle of spectral accuracy, high throughput, and economic design. We also discuss the general considerations, which helps the community reassess the utility of the different Raman spectrometer designs.